HUBUNGAN PENDAPATAN KELUARGA DENGAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR DIKOTA MANADO - Parengkuan, Rendy R.; Mayulu, Nelly; Ponidjan, Tati (JURNAL KEPERAWATAN)
Abstract: Obesity is an increase in body fat due more less. Obesitas positive energy balance, as a result of an imbalance between energy intake with energy output, resulting in excess energy is stored as fat tissue This study aimed to analyze the relationship of family income to the incidence of obesity in primary school children in Manado city with analytical survey method using a control sample of 136 Case design using chi-square test (x2), at the 95% significance level (α 0.05). Results showed that there is a relationship between family income to the incidence of obesity in elementary school children in the city of Manado. Conclusion results showed that most of the students in the case group (obesity) is the category of high-income families. Similarly, students in the control group (not obese) are mostly located in the category of low income families. Families with children who have high incomes have 3 times the risk of being obese.Suggestions provide information about obesity and obesity further planning on Scaling back monitoring the nutritional status of children especially elementary school students to monitor the growth and development of nutritional status. Keywords: family income, obesity Abstrak: Obesitas adalah peningkatan lemak tubuh yang berlebihan.Obesitas disebabkan adanya keseimbangan energi positif, sebagai akibat ketidak seimbangan antara asupan energi dengan keluaran energi, sehingga terjadi kelebihan energi yang disimpan dalam bentuk jaringan lemak Penelitian ini bertujuan menganalisis hubungan pendapatan keluarga dengan kejadian obesitas pada  anak SD di kota Manado dengan metode penelitian survei analitik dengan menggunakan  rancangan Case control sampel 136 menggunakan uji chi-square (x2), pada tingkat kemaknaan 95%   (α 0,05).Hasil penelitian menunjukan bahwa terdapat hubungan antara pendapatan keluarga dengan kejadian obesitas pada anak SD di kota Manado kesimpulan Proporsi keluarga berpendapatan  tinggi  yang memiliki anak obesitas sebesar 55,9 % dan pada kelompok tidak obesitas 25%.Keluarga dengan pendapatan tinggi merupakan faktor resiko terjadinya obesitas pada anak SD di Kota Manado( OR=3,8).) saran memberikan informasi tentang obesitas dan perencanaan lebih lanjut mengenai obesitas Menggiatkan kembali monitoring status gizi anak sekolah terutama siswa SD untuk memantau pertumbuhan dan perkembangan status gizinya Kata kunci: pendapatan keluarga, obesitas